2023
DOI: 10.3390/ani13182830
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of 1-Deoxynojirimycin from Mulberry on Oxidative Stress and Inflammation in Laying Hens and the Direct Effects on Intestine Epithelium Cells In Vitro

Mingzhu Wang,
Yuan Feng,
Tao Li
et al.

Abstract: The intestine is highly vulnerable to various factors and has been proposed as a promising determinant for poultry health. Phytogenic or plant-derived feed additives can be used to help improve intestinal health. In this study, we aimed to investigate the effects of DNJ on the antioxidative parameters, including malondialdehyde (MDA), total superoxide dismutase (T-SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and inflammatory cytokines (IL-6, IL-1β, and TNF-α), in plasma and intestinal tissues using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…Previous animal studies indicated that DNJ treatment attenuates cellular oxidative stress by upregulating the expression of detoxification enzymes with the capability to scavenge ROS, for example, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) [35]. Wang et al found that DNJ treatment upregulated the mRNA levels of NRF2 in chicken intestinal epithelial cells [25]. NRF2 is an important regulator of cellular oxidative status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous animal studies indicated that DNJ treatment attenuates cellular oxidative stress by upregulating the expression of detoxification enzymes with the capability to scavenge ROS, for example, superoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GSH-Px) [35]. Wang et al found that DNJ treatment upregulated the mRNA levels of NRF2 in chicken intestinal epithelial cells [25]. NRF2 is an important regulator of cellular oxidative status.…”
Section: Discussionmentioning
confidence: 99%
“…In a recently published animal study, Wang et al reported that a diet supplemented with DNJ extract from mulberry leaves increased the anti-oxidative index in the plasma and intestinal tissues of hens. Their cell studies, using hen intestine epithelial cells, indicated that DNJ increased the level of NRF2 mRNA, and enhanced the expression of reactive species scavenging enzymes including SOD and catalase [25]. Yu et al observed that mulberry extract as a food supplement upregulated NRF2 protein in the liver tissue of inflammation model rats challenged with lipopolysaccharide [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation